AB0103 Acute pancreatitis as initial manifestation of anti-phospholipid syndrome. (1st June 2001) - Qu, J; Kankwenda, K; Ooghe, P; Gregoir, C
Abstract : Background: A 17 years old Belgian man was admitted with acute non-necrotic pancreatitis. Laboratory data showed high levels of amylase and lipase, leucocytosis, erythrocyte sedimentation rate (ESR) 24 mm/h and CRP 8.7 mg/100 ml, IgM against Epstein-Barr Virus (EBV) and lupus anticoagulant (detected according to the guidelines of International Society on Thrombosis and Haemostasis) were present. The evolution was spontaneously favourable and the diagnosis of acute pancreatitis on EBV infection was retained. Objectives: Four months later, recurrent abdominal pain appeared and the only positive clinical finding was a livedo reticularis. Laboratory test showed a high ESR (63 mm/h) but a normal CRP (0.2 mg/100 ml), haemolytic anaemia, leucopenia, hypocomplementemia, presence of lupus anticoagulant, antinuclear antibody at 1/640 with anti dsDNA 517, EBV IgM antibody title has not changed. Neither cutaneous nor renal involvement nor serositis was observed. Mesenteric angioCT was normal. The patient recovered under a treatment of steroids, anticoagulation and hydroxychloroquine. Methods: Results: Pancreatitis is a rare manifestation in the anti-phospholipid syndrome (APS) or systemic lupus erythematosus (SLE) and is often associated with severe multi-systemic complication and of poor prognosis. Although the aetiology is not known, vasculitis lesion and thrombosis, adverse effect of steroid and azathioprine were thought to be the cause. Conclusion: We describe a case of pancreatitis as initial manifestation of APS, since ACR criteria for SLE are not fulfilled. No further complication was observed at 2 months? follow-up. The presence of EBV IgM antibody is probably due to polyclonal activation. References: Saab S, et al . Corticosteroids and systemic lupus erythematosus pancreatitis: a case series. J Rhumatol. 1998;25(4):801–6 Rojas-Serrano J, et al . Lupus patients in an emergency unit. Causes of consultation, hospitalization and outcome. A cohort study. Lupus 2000;9(8):601–6